Reconstruction: Beyond C-Command - Shaheen , Buthaina (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This paper criticises specific syntactic arguments about the phenomenon of reconstruction that have been widely endorsed, specifically those that involve c-command as a pre-requisite for any interpretation of the phenomenon. It also discusses some arguments that took semantics into consideration in interpreting reconstruction. The paper illuminates the fact that arguments based solely on syntax, specifically c-command are problematic, and that other fields: morphology and semantics are essential for a proper analysis of the phenomenon.